2004
DOI: 10.1002/chem.200400747
|View full text |Cite
|
Sign up to set email alerts
|

Complete Charge Pooling is Prevented in Viologen‐Based Dendrimers by Self‐Protection

Abstract: We have investigated the electrochemical behavior, and chemical and photosensitized reduction of two dendrimers based on a 1,3,5-trisubstituted benzenoid core, which contain 9 and 21 4,4'-bipyridinium (usually called viologen) units, respectively, in their branches and are terminated with tetraarylmethane groups. For comparison purposes, the behavior of reference compounds that contain a single viologen unit have also been investigated. We have found that only part of the viologen units can be reduced in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 60 publications
1
44
0
Order By: Relevance
“…Several dendrimers are capable of storing several redox equivalents [185] and, in some cases, the reduction process can be carried out by photoexcitation. [186] Artificial photosynthetic systems could be realized by connecting catalysts for water reduction and oxidation to a photovoltaic cell (Section 5.2). [13,187] In such constructs, the spatially separated electron-hole pairs provided by the photovoltaic junction are captured by the catalysts, and the energy is stored in the bond rearrangement of water to H 2 and O 2 .…”
Section: Other Systemsmentioning
confidence: 99%
“…Several dendrimers are capable of storing several redox equivalents [185] and, in some cases, the reduction process can be carried out by photoexcitation. [186] Artificial photosynthetic systems could be realized by connecting catalysts for water reduction and oxidation to a photovoltaic cell (Section 5.2). [13,187] In such constructs, the spatially separated electron-hole pairs provided by the photovoltaic junction are captured by the catalysts, and the energy is stored in the bond rearrangement of water to H 2 and O 2 .…”
Section: Other Systemsmentioning
confidence: 99%
“…A different behavior, however, has been observed for two families of dendrimers that only differ in the peripheral groups (Fig. 14) [69][70][71]. Electrochemical experiments have indeed revealed that in all cases only a fraction of the viologen units can be reduced, and that this fraction corresponds (within experimental error) to the number of the viologen units present in the outer shell (six for A9 18þ and B9 18þ , and 12 for A21 42þ and B21 42þ ).…”
Section: The Beauty Of Chemistry In the Words Of Writers And In The Hmentioning
confidence: 89%
“…Nowadays the miniaturization race leads scientists to [69][70][71] The Beauty of Chemistry in the Words of Writers and in the Hands of Scientists 91 investigate the possibility of designing and constructing machines at the nanometer scale, i.e., at the molecular level. Molecular machines are already present in Nature (e.g., ATP synthase) [74], but they are extremely complex systems; any attempt to construct systems of such a complexity by using the bottom-up molecular approach would be hopeless.…”
Section: Molecular Machinesmentioning
confidence: 99%
“…85 In relation to this, recently, a series of poly-(viologen) dendrimers with different numbers of viologen units have been synthesized by Marchioni and coworkers to investigate the stepwise photoreduction of viologen arrays in the bulky dendrimer framework. 86 A well-defined three-dimensional structure along with a precise location of functional groups in its framework makes dendritic macromolecule a promising motif for the investigation of photoinduced electron transfer event at the single molecular level. Recently, De Schryver and coworkers have explored this possibility by using rigid polyaryl dendrimers 70 and 71 with peryleneimide core as electron acceptor and arylamine units on the surface as electron donor, upon embedded in a polystyrene matrix.…”
Section: Other Dendritic Pet Systemsmentioning
confidence: 99%